2017
DOI: 10.1590/0100-29452017787
|View full text |Cite
|
Sign up to set email alerts
|

BOTÂNICA E FISIOLOGIA/ BOTANY AND PHYSIOLOGY ANTIOXIDANT ACTIVITY AND PHYSICOCHEMICAL PARAMETERS IN ‘CUERNAVAQUEÑA’ MEXICAN PLUM (Spondias purpurea L.) AT DIFFERENT RIPENING STAGES

Abstract: -Mexican plum (Spondias purpurea L.) 'Cuernavaqueña' was harvested at four ripening stages, with the aim of evaluating the concentration of bioactive compounds and antioxidant capacity in the pulp and the epicarp. The highest ethylene production (9.43 mL kg h -1 ) and total soluble solids concentration (23.9 °Brix) was observed in the fully ripe stage. Titratable acidity was higher in green stage compared to other analyzed ripening stages in both pulp (0.48 %) and epicarp (0.32 %). Fully ripe plum epicarp pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…2017). These results are in support with those reported by Dantas et al (2016) The ½ green and the ¾ ripe fruit stages contained higher total phenols concentrations in the pulp, 89.21 and 77.7 mg GAE 100 g -1 respectively, compared to the green and fully ripe stages (Vargas et al, 2017). However, the fully ripe stage showed the highest total phenols concentration in the epicarp (190.6 mg GAE 100 g -1 ).…”
Section: Physicochemical Changes During Ripeningsupporting
confidence: 92%
See 4 more Smart Citations
“…2017). These results are in support with those reported by Dantas et al (2016) The ½ green and the ¾ ripe fruit stages contained higher total phenols concentrations in the pulp, 89.21 and 77.7 mg GAE 100 g -1 respectively, compared to the green and fully ripe stages (Vargas et al, 2017). However, the fully ripe stage showed the highest total phenols concentration in the epicarp (190.6 mg GAE 100 g -1 ).…”
Section: Physicochemical Changes During Ripeningsupporting
confidence: 92%
“…Colour parameters in the epicarp of Mexican plum showed significant (P<0.05) changes among the four ripening stages (Vargas et al, 2017), similar to that reported by Dantas et al (2016). The colour measurements of the green stage revealed that the epicarp was green (ho=108.9), dull (C*=26.4) and slightly bright (L*= 39.9) compared to the ½ green stage which was close to yellow (ho=93.7), less dull (C*=34.4) and brighter, and in the ¾ ripe stage, where fruits displayed an angle hue approaching orange (ho= 75.3) with a chromaticity of (C*= 43.4) and enhanced brightness (L*= 50.3).…”
Section: Physicochemical Changes During Ripeningmentioning
confidence: 94%
See 3 more Smart Citations